Access to justice in South Africa: are there enough lawyers? - McQuoid-Mason, David Jan (Oñati Socio-Legal Series, 2013)
This paper addresses head on the contention by a prominent legal practitioner in South Africa that there are too many lawyers in the country. It does not canvass the complex issues involved in determining the meaning of access to justice or the relationship between law and society in the context of legal services, and deals with access to justice in the narrow sense of the delivery of legal services in South Africa. The paper analyses the evidence presented to substantiate the contention that there are too many lawyers against the socio-economic environment in South Africa and the requirements of the Constitution. It recognizes that the country has only a minority of people who can afford lawyers and compares the ratio of lawyers to people in this category with the ratio in other developed countries. It also recognizes that large numbers of people who cannot afford lawyers may need them and that such people will have to rely largely on the state-funded national legal aid body, Legal Aid South Africa and other mechanisms. The paper discusses the different modes of delivery of legal aid services by Legal Aid South Africa, as well as those provided by the legal profession pro bono, public interest law firms and mechanisms that compliment or are alternatives to lawyers, in the light of the number of practicing lawyers in the country. An analysis is made to determine if there are enough lawyers to provide the necessary legal services required by the Constitution in criminal matters, and for civil matters in general for those who can and cannot afford lawyers. The paper concludes that there are not enough lawyers in the country at present to provide access to justice in the narrow sense, and suggests how this shortage can be overcome by using mechanisms that provide alternatives to lawyers.